2021
DOI: 10.26434/chemrxiv-2021-bv7tb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiscale simulations identify origins of differential carbapenem hydrolysis by the OXA-48 β-lactamase

Abstract: OXA-48 β-lactamases are frequently encountered in bacterial infections caused by carbapenem-resistant Gram-negative bacteria. Due to the importance of carbapenems in treatment of healthcare-associated infections, and the increasingly wide dissemination of OXA-48-like enzymes on plasmids, these β-lactamases are of high clinical significance. Notably, OXA-48 hydrolyses imipenem more efficiently than other commonly used carbapenems, such as meropenem. Here, we use extensive multi-scale simulations of imipenem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…When the 6α-1R-hydroxyethyl group instead accepts a H-bond from the DW (as observed with OXA-48/imipenem), hydrolysis is more efficient. 48 Role of Asn132. The most significant difference between BlaC and other class A β-lactamase active sites is the lack of Asn132 in the former, in which it is replaced by Gly.…”
Section: ■ Resultsmentioning
confidence: 99%
“…When the 6α-1R-hydroxyethyl group instead accepts a H-bond from the DW (as observed with OXA-48/imipenem), hydrolysis is more efficient. 48 Role of Asn132. The most significant difference between BlaC and other class A β-lactamase active sites is the lack of Asn132 in the former, in which it is replaced by Gly.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Most of the variants in the OXA-48 family are carbapenemases, with elevated IME hydrolysis rates when compared against other carbapenems. 59 For OXA-48, experimental measurements of k cat values for IME hydrolysis vary between 1.5 and 22.5 s −1 , which can be converted to free energy barriers for activation (Δ ⧧ G) from 15.7 to 17.3 kcal/mol using the Eyring equation. For MER, the measured k cat values range between 0.07 and 0.16 s −1 , which converts to barriers from 18.7 to 19.2 kcal/mol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar to acylation and reverse acylation reactions, a general base-catalyzed mechanism was also proposed for this reaction. The deprotonated carbamylated Lys73 was presumed to be the general base for activating the hydrolytic water molecule. , Lahiri et al suggested that the carbamylated Lys73 is in a protonated form in the EI1 state formed by avibactam. Thus, it fails to activate the hydrolytic water molecule and thereby inhibits the hydrolysis .…”
Section: Resultsmentioning
confidence: 99%